2012
DOI: 10.1029/2011pa002187
|View full text |Cite
|
Sign up to set email alerts
|

Glacial‐interglacial size variability in the diatom Fragilariopsis kerguelensis: Possible iron/dust controls?

Abstract: [1] The valve area of Fragilariopsis kerguelensis, the most abundant diatom species in the Southern Ocean, strongly changes in size in response to varying conditions in the surface ocean. We examined the link, both in two iron fertilization experiments and in sediment samples covering several glacial Terminations, between size variability in this species and environmental conditions across the Antarctic Polar Front, including sea ice extent, sea surface temperature, and the input of eolian dust. The iron ferti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 58 publications
(84 reference statements)
0
32
0
Order By: Relevance
“…The authors related the presence of F. kerguelensis populations with larger average cell size to alleviation of iron limitation during iron-replete glacial conditions (Cortese & Gersonde, 2007). The possible link between glacialinterglacial changes in the average cell size of F. kerguelensis and iron availability (cells with a larger valvar area occurring in glacial periods characterized by a higher Fe deposition from atmospheric dust) was further confirmed by Cortese et al (2012). The authors also reported a larger valvar area for F. kerguelensis inside fertilized patches of two iron-fertilization experiments.…”
Section: Fragilariopsis Kerguelensis As a Palaeo-proxy: A Life Cycle mentioning
confidence: 52%
See 2 more Smart Citations
“…The authors related the presence of F. kerguelensis populations with larger average cell size to alleviation of iron limitation during iron-replete glacial conditions (Cortese & Gersonde, 2007). The possible link between glacialinterglacial changes in the average cell size of F. kerguelensis and iron availability (cells with a larger valvar area occurring in glacial periods characterized by a higher Fe deposition from atmospheric dust) was further confirmed by Cortese et al (2012). The authors also reported a larger valvar area for F. kerguelensis inside fertilized patches of two iron-fertilization experiments.…”
Section: Fragilariopsis Kerguelensis As a Palaeo-proxy: A Life Cycle mentioning
confidence: 52%
“…Valve morphometrics of Fragilariopsis kerguelensis have been suggested to have potential for reconstructing palaeo-oceanographic conditions in the Southern Ocean, based on the fact that the average frustule size varies amongst sites characterized by different productivity regimes (Cortese & Gersonde, 2007;Crosta, 2009;Cortese et al, 2012). Cortese & Gersonde (2007) analysed the valve length and valve area of F. kerguelensis frustules in surface sediments from the Pacific and Atlantic sectors of the Southern Ocean (providing a spatial gradient) and one piston core (giving a temporal gradient) near the Antarctic Polar Front.…”
Section: Fragilariopsis Kerguelensis As a Palaeo-proxy: A Life Cycle mentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the down-core records from the Atlantic and Indian Antarctic Polar Front (APF), and Atlantic and Indian Sub-Antarctic Front (SAF) show larger F. kerguelensis mean valve area (FkergArea) throughout the last glacial period during higher aeolian dust flux to the SO. FkergArea generally declined during the deglacial and the Holocene periods along with a reduction in the dust flux (Cortese & Gersonde 2007, Cortese et al 2012, Shukla et al 2013. This pattern was reproducible until termination V,~430 cal kyrs BP (Cortese et al 2012).…”
Section: Introductionmentioning
confidence: 88%
“…Fragilariopsis kerguelensis (O'Meara) Hustedt is the most abundant diatom species in the surface sediments and in the down-core records of the open Southern Ocean (SO) (Zielinski & Gersonde 1997, Crosta et al 2005a and is believed to be a major silica carrier to the sea floor (Cortese & Gersonde 2008, Abelmann et al 2015. Fragilariopsis kerguelensis size variability has recently been proved useful to infer recent (Cortese & Gersonde 2007) and past oceanic conditions at the glacialinterglacial timescales (Cortese et al 2012, Shukla et al 2013, Nair et al 2015. A study conducted on sediment traps and surface sediments from the sea-ice zone to the subtropical zone of the Atlantic SO suggested a strong correlation of F. kerguelensis size with iron availability (Cortese & Gersonde 2007), consistent with the findings of culture experiments (Assmy et al 2006, Timmermans & van der Wagt 2010 and in situ iron fertilization experiments (Assmy et al 2007).…”
Section: Introductionmentioning
confidence: 99%